AutoCAD 2010 : a problem-solving approach - 401471 Tickoo, Sham (Clifton Park, NY : Delmar/Cengage Learning)
Introduction to AutoCAD -- Getting started with AutoCAD -- Starting with the advanced sketching -- Working with drawing aids -- Editing sketched objects I -- Editing sketched objects II -- Creating text and tables -- Basic dimensioning, geometric dimensioning, and tolerancing -- Editing dimensions -- Dimensions styles, multileader styles, and system variables -- Adding constraints to sketches -- Model space viewports, paper space viewports, and layouts -- Template drawings -- Plotting drawings -- Hatching drawings -- Working with blocks -- Defining block attributes -- Understanding external references -- Working with advanced drawing options -- Grouping and advanced editing of sketched objects -- Working with data exchange and object linking and embedding -- Technical drawing with AutoCAD -- Isometric drawings -- The user coordinate system -- Getting started with 3D -- Creating solid models -- Modifying 3D objects -- Editing 3D objects -- Mesh modeling -- Rendering and animating designs